(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
The order Caryophyllales exhibit diverse diversity in morphology to molecules, which leads to taxonomic complexities in circumscribing especially to its families. The comparative analysis of the available chloroplast genome to detect pattern of genomic arrangement and variation is lacking; hence, the alignment pattern and genomic rearrangement across the Caryophyllales were detected, and the phylogenetic relationship among the families of the Caryophyllales based on maximum cp genes were inferred. The comparison of the Caryophyllales cp genomes based on representatives of 10 families with Taxillus chinensis as reference genome revealed that coding region were more conserved than the non-coding region; however, clpP, rpl16 and ycf15 were the most divergent coding region among all taxa. Further, the genomic rearrangement occurred in gene organization of the taxa among different families of Caryophyllales, the extensive rearrangement were observed in Amaranthaceae, Caryophyllaceae, Chenopodiaceae, Droseraceae and Cactaceae.